Neonatal Tracheostomy – Issues and Solutions - Saadia, A; Prasad, GR (Journal of Neonatal Surgery, 2015)
AIMS: To record and analyse the technical aspects of neonatal tracheostomy and to suggest some solutions. Materials and Methods: This is a retrospective observational cohort of 37 cases of neonatal tracheostomies performed over 30 years (1985-2014). Results: Thirty-three of the 37 tracheostomies were done as an elective procedure and four done emergently. Eighteen neonatal tracheostomies were done with a low transverse cervical incision and 19 were done with low vertical cervical incision. Three patients had bleeding while exposing the trachea. Trachea could not easily be identified in 2 cases. Commercial tracheostomy tubes were used in only 20 cases. In 17 patients, the conventional endotracheal tubes 2.5 or 3fr size were used. There were 3 instances of wound infection out of which one has peri-tracheostomy necrotizing cellulitis and the neonate succumbed to sepsis. Two cases had surgical emphysema. No case had pneumothorax. Conclusion: We described tracheostomy in neonates in a resource constrained centre. Various makeshift arrangements can be used in absence of standard supplies.